Pengaruh Sosial Media Marketing dan Event Marketing Terhadap Minat Mahasiswa Baru Memilih Kampus STIE Bima - Ahmad Bani Adam; Muhajirin; Intisari Haryanti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to analyze the influence of social media marketing and event marketing on the interest of new students in choosing STIE Bima. The method used is associative research with data collection through surveys of 127 new students. The results of the regression analysis indicate that social media marketing and event marketing have a positive relationship with theinterest of new students, although the impact is not significant. This study recommends STIE Bima to enhance its marketing strategies to attract more new students. Further research is suggested to explore the relationship between marketing strategies and student enrollment in greater depth